Pellino1 Is Required for Interferon Production by Viral Double-stranded RNA - Enesa, Karine (American Society for Biochemistry and Molecular Biology, 2012)
Viral double-stranded RNA, a ligand for Toll-like Receptor 3 (TLR3) and the cytoplasmic RNA receptors RIG1 and MDA5, activate a signaling network in which the IKK-related protein kinase TBK1 phosphorylates the transcription factor Interferon Regulatory Factor 3 (IRF3) and the E3 ubiquitin ligase Pellino1. IRF3 then translocates to the nucleus where it stimulates transcription of the interferonβ (IFNβ) gene, but the function of Pellino1 in this pathway is unknown. Here, we report that myeloid cells and embryonic fibroblasts from knock-in mice expressing an E3 ligase-deficient mutant of Pellino1 produce reduced levels of IFNβ mRNA and secrete much less IFNβ in response to viral double-stranded RNA because the interaction of IRF3 with the IFNβ promoter is impaired. These results identify Pellino1 as a novel component of the signal transduction network by which viral double-stranded RNA stimulates IFNβ gene transcription.